Screening for inhibitors of Staphylococcal Sortase A as novel anti-infective agents - Tong, Carmen (2018)
Staphylococcus aureus is a Gram-positive human pathogen that has developed resistance to all traditionally used antibiotics. Sortase A (SrtA) is a ‘house-keeping’ enzyme present in a number of Gram-positive organisms including S. aureus that is responsible for the covalent anchoring of proteins to the cell wall through the recognition of a highly conserved LPXTG motif. Many of the proteins it anchors are involved in virulence and immune evasion suggesting that it is an attractive target for potential anti-infective therapies. Moreover, as SrtA is not vital for bacterial growth or survival, inhibition may not select for the development of drug-resistance, unlike conventional antibiotics.